DELIVERING GAMIFICATION TO OVERCOME FINANCIAL PROBLEMS DURING A PANDEMIC - Alfina Rahmatia; Arief Dwi Saputra; Sri Handari Wahyuningsi (Universitas Airlangga, 2021)
Gamification is a game design in a non-game context that can be applied to the UMKM business. This study investigates how gamification strategies can play a role in entrepreneurial behavior on attitudes, subjective norms and behavior control, and entrepreneurship education through self-efficacy, experience, and program involvement. The method in this study used a qualitative research strategy with a sample of 442 respondents. First, the root of the problem is reviewed from the literature review and strengthened by collecting data from the in-depth interview process. Furthermore, the data is processed using the Nvivo 12 application with word similarity analysis then the results of the study are used as a reference and conclusion through the data obtained. Finally, based on these results, research contributions are used to answer problems in the Organization's role to solve the relationship between gamification strategies for employee performance in improving entrepreneurial behavior and strengthening entrepreneurial education activities. The findings in this study indicate that the application of gamification with a total percentage of 100% can be used as a strategy for UMKM business recovery in the new normal era as a whole on each element that supports each other to have an impact on motivation, behavior change and psychological effects.